The inter-rater reliability and prognostic value of coma scales in Nepali children with acute encephalitis syndrome. (2nd January 2018) - Ray, Stephen; Rayamajhi, Ajit; Bonnett, Laura J.; Solomon, Tom; Kneen, Rachel; Griffiths, Michael J.
Abstract: Background: Acute encephalitis syndrome (AES) is a common cause of coma in Nepali children. The Glasgow coma scale (GCS) is used to assess the level of coma in these patients and predict outcome. Alternative coma scales may have better inter-rater reliability and prognostic value in encephalitis in Nepali children, but this has not been studied. The Adelaide coma scale (ACS), Blantyre coma scale (BCS) and the Alert, Verbal, Pain, Unresponsive scale (AVPU) are alternatives to the GCS which can be used. Methods: Children aged 1–14 years who presented to Kanti Children's Hospital, Kathmandu with AES between September 2010 and November 2011 were recruited. All four coma scales (GCS, ACS, BCS and AVPU) were applied on admission, 48 h later and on discharge. Inter-rater reliability (unweighted kappa) was measured for each. Correlation and agreement between total coma score and outcome (Liverpool outcome score) was measured by Spearman's rank and Bland–Altman plot. The prognostic value of coma scales alone and in combination with physiological variables was investigated in a subgroup ( n  = 22). A multivariable logistic regression model was fitted by backward stepwise. Results: Fifty children were recruited. Inter-rater reliability using the variables scales was fair to moderate. However, the scales poorly predicted clinical outcome. Combining the scales with physiological parameters such as systolic blood pressure improved outcome prediction. Conclusion: This is the first study to compare four coma scales in Nepali children with AES. The scales exhibited fair to moderate inter-rater reliability. However, the study is inadequately powered to answer the question on the relationship between coma scales and outcome. Further larger studies are required.